Career decision making among young graduates: Self-initiated expatriation perspective - Miettinen, Elina (My University, 2008)
Internationalisation and globalisation have changed the way of doing business and there is a growing need for talented and internationally oriented employees. There are more and more companies that have realised that they will gain competitive advantage in this turbulent world by sending their employees abroad to work. There is a lot of research done on these expatriates but in this study the focus is on self-initiated expatriates (SEs) who are not sent abroad by a certain company. These SEs make the career decision to internationalise their career by themselves. In this study the young graduates are in a special focus. The career decision-making process of these young graduates has not been studied before and the goal of this study is to find out different reasons that are influencing the career decision-making process of these young graduates. The theoretical framework of this study is based on the new career theory, the theory of self-initiated expatriation, the theory of career decision-making process and Schein’s career anchor theory. The theoretical framework aims at defining the main motivational factors and career anchors influencing the career decision-making process of a young graduate when he or she makes a decision to internationalise his or her career. As these careers can be seen as boundaryless careers, the boundaryless career theory is also introduced. The interviews were made by using a focused interview method. The average age of the respondents was 28 years and all of the respondents had made the decision to internationalise their careers in a year after their graduation. There is no earlier research on young graduates, but the results of this study are in line with earlier research that was made among global managers. It was clearly seen that ‘internationalisation’ career anchor was the main motive affecting the decision to work abroad. The growing importance of boundaryless career theory and the characteristics of self initiated expatriates were also confirmed.
Keywords: self-initiated expatriate; boundaryless career; career anchor; career decision-making; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|